2017
DOI: 10.1007/s11356-017-9342-5
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of potentially toxic elements (PTEs) in tailings, soils, and plants around Gol-E-Gohar iron mine, a case study in Iran

Abstract: This study investigated the concentration of potentially toxic elements (PTEs) including Al, As, Cd, Co, Cr, Cu, Fe, Hg, Mn, Mo, Ni, Pb, Sb, V, and Zn in 102 soils (in the Near and Far areas of the mine), 7 tailings, and 60 plant samples (shoots and roots of Artemisia sieberi and Zygophylum species) collected at the Gol-E-Gohar iron ore mine in Iran. The elemental concentrations in tailings and soil samples (in Near and Far areas) varied between 7.4 and 35.8 mg kg−1 for As (with a mean of 25.39 mg kg−1 for tai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 127 publications
1
18
2
Order By: Relevance
“…However, the individual result of each site indicated that the concentration of Cu at Dujiatian site exceeded the permissible limit of FAO/ISRIC (2004), WHO/FAO (2001) and USEPA (1983). As compared to the other studies the mean concentration value of Cu (60.73 mg/kg)was less than the finding in Brazil (111.54 mg/kg) [62], Wuhan, China (60.85 mg/kg) [33], Hubei Province, China (386mg/kg), Democratic Republic of Congo (10,320 mg/kg) [67], Iran (100.84 mg/kg) [64], but the result was higher than the findings in soil from Cuba (43.10 mg/kg) [59], Bangladesh (20.6 mg/kg) [11], India (52.72 mg/kg) [61], Tanzania (5.62 mg/kg) [10], Pakistan (18.12 mg/kg) [63], Northern Pakistan (35.28 mg/kg) [66] and in soil along the Chao River in China (46.5 mg/kg) [65].…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…However, the individual result of each site indicated that the concentration of Cu at Dujiatian site exceeded the permissible limit of FAO/ISRIC (2004), WHO/FAO (2001) and USEPA (1983). As compared to the other studies the mean concentration value of Cu (60.73 mg/kg)was less than the finding in Brazil (111.54 mg/kg) [62], Wuhan, China (60.85 mg/kg) [33], Hubei Province, China (386mg/kg), Democratic Republic of Congo (10,320 mg/kg) [67], Iran (100.84 mg/kg) [64], but the result was higher than the findings in soil from Cuba (43.10 mg/kg) [59], Bangladesh (20.6 mg/kg) [11], India (52.72 mg/kg) [61], Tanzania (5.62 mg/kg) [10], Pakistan (18.12 mg/kg) [63], Northern Pakistan (35.28 mg/kg) [66] and in soil along the Chao River in China (46.5 mg/kg) [65].…”
Section: Resultsmentioning
confidence: 78%
“…The mean concentration value of Co (22,656.94 mg/kg) was above the permissible limit of FAO/ISRIC (2004) and WHO/FAO (2001) (Table 2). Compared to other findings the mean concentration of Co was higher than the study in Cuba (9.16 mg/kg) [59], Brazil (7.44 mg/kg) [62], Pakistan (7.56 mg/kg) [63], Wuhan (China) (16 mg/kg) [32] and (16.37 mg/kg) [33], Iran (38.5, 16.51 mg/kg) [64], Chao River China (17.5 mg/kg) [65] and Northern Pakistan (36.76 mg/kg) [66].…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Clifford and Barton [39] reported that O'Kiep's soil is rich in bornite Cu₅FeS₄; as evidenced by the high concentration values of S and Cu. From the literature reviewed, it was reported that distance from the pollution source and weather-related matters, play significant roles in the exposure to metalloids and metals [40]. PTE concentrations in the upstream showed that contaminant concentrations were higher near the close metalliferous mine than downstream.…”
Section: B Major Oxides and Potential Toxic Elementsmentioning
confidence: 99%
“…Most trace metals pose serious environmental and health risks because they are toxic and could become labile when the normal threshold is exceeded and they are exposed to the environment [12]. Both heavy metals and metalloids are contaminants in mining and smelting areas as they accumulate in soils, plants, and water streams, posing serious threats to the ecosystem health and nearby habitats, including fauna, flora, and microfauna [13][14][15]. Most of these effects persist over large expanses of land, even long after mining activities have ceased [2,16].…”
Section: Introductionmentioning
confidence: 99%